A Case of Aural Atresia - Polat, Cahit; Baykara, Murat; Sakallıoğlu, Öner; Soylu, Erkan; Yüce, Salim; Akyiğit, Abdulvahap (Fırat University, 2013)
Congenital aural atresia (CAA), pinna, external auditory canal and middle ear deformities is a developmental anomaly in the area. Otoscopic examination in patients with stenosis or atresia of external auditory canal is also not possible. Therefore, the evaluation of these cases high-resolution computed tomography (HRCT) examination is an important option. It also examined to determine suitable candidates for surgery in the planning and operation may lead the way. We wanted to emphasize the importance of HRCT in this case offered the membranous aural atresia.

Konjenital aural atrezi (KAA) kulak kepçesi, dış kulak yolu ve orta kulak deformitelerini içine alan gelişimsel bir anomalidir. Dış kulak yolunda darlık veya atrezi olan olgularda otoskopik muayene de mümkün değildir. Bu yüzden bu olguların değerlendirilmesinde yüksek rezolüsyonlu bilgisayarlı tomografi (YRBT) tetkiki önemli bir seçenektir. Bu tetkik cerrahiyi planlamada ve operasyon için uygun adayların belirlenmesinde de yol gösterici olabilir. Sunulan membranöz aural atrezili bu olguda YRBT'nin önemini vurgulamak istedik.
Aural Atrezi Olgusu